2014
DOI: 10.1186/1465-9921-15-42
|View full text |Cite
|
Sign up to set email alerts
|

Impact of inflammation, emphysema, and smoking cessation on V/Q in mouse models of lung obstruction

Abstract: BackgroundChronic obstructive pulmonary disease (COPD) is known to greatly affect ventilation (V) and perfusion (Q) of the lung through pathologies such as inflammation and emphysema. However, there is little direct evidence regarding how these pathologies contribute to the V/Q mismatch observed in COPD and models thereof. Also, little is known regarding how smoking cessation affects V/Q relationships after inflammation and airspace enlargement have become established. To this end, we have quantified V/Q on a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 25 publications
1
11
0
Order By: Relevance
“…Mice were housed at 23 • C on a 12:12 h light-dark cycle (lights on 07:00 h) under specific pathogenfree conditions and provided food and water ad libitum. We opted to use female mice as we have previously validated the cigarette smoke exposure model in females (Jobse et al, 2013(Jobse et al, , 2014. Following telemetry implantation, animals were housed individually in Faraday cages connected to telemetry receivers (RPC-1; Data Science International).…”
Section: Ethical Approvalmentioning
confidence: 99%
“…Mice were housed at 23 • C on a 12:12 h light-dark cycle (lights on 07:00 h) under specific pathogenfree conditions and provided food and water ad libitum. We opted to use female mice as we have previously validated the cigarette smoke exposure model in females (Jobse et al, 2013(Jobse et al, , 2014. Following telemetry implantation, animals were housed individually in Faraday cages connected to telemetry receivers (RPC-1; Data Science International).…”
Section: Ethical Approvalmentioning
confidence: 99%
“…Animal models utilizing cigarette smoke exposure display the characteristic features of human COPD including accumulation of inflammatory cells, small airway fibrosis/remodeling, mucus hyper-secretion, lung dysfunction and development of emphysema [ 3 ]. In mouse models of COPD, chronic exposure of mice to cigarette smoke triggers typical pathological hallmarks of the disorder, such as pulmonary inflammation, airway remodeling and airspace enlargement caused by the destruction of alveolar walls [ 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“… 21 In addition, we showed that C3d deposition could be identified in the RPE, BrM, and choriocapillaris, which was correlated with alterations in gene expression of complement components in the RPE-choroid fraction of the eye (increase in activators and a decrease in complement inhibitors). 21 Using a novel model of smoking cessation, 22 24 we expanded on these findings by investigating whether the detrimental effects caused by CSE are reversible following smoking cessation and treatment with the tissue-targeted AP inhibitor, CR2-fH. 25 CR2-fH consists of the N-terminus of mouse complement factor H (short consensus repeats [SCR] 1–5), which contains the AP-inhibitory domain, linked to a complement receptor 2 (CR2) targeting fragment that binds complement activation products.…”
mentioning
confidence: 99%